Asy-Syekh Adam Abdullah Al-Ilwari Wa Manhajuhu fi I'dad Asy-Syu'ara' - Hamid, M. Abdul; Ibraheem, Lateef Onireti (UIN Maulana Malik Ibrahim Malang, 2007)
The development and spread of Arabic literary works cannot be separated from the founder and its figures both from Arabic spoken-country and non-Arabic one. Syaikh Adam Abdullah al Ilori is one of the figures in Nigeria that has significant role in spreading Arabic literary works and at once educating the next generation as litterateur and the expert of Arabic literature in Nigeria. In line with the aim, there are five strategies developed by Syaikh Adam al Ilori; 1) memorization, b) direct teaching of Arabic literary works, c) teaching the principles of aruud, d) training to create the Arabic poems, and e) holding competition to encourage young poets. These five strategies are effective to be applied in Nigeria in aiming for spreading Arabic literature and creating the expert of it so that many writers were born in Nigeria such as Abu Bakar Umar, Roji Suliman, Abdul Baqi Syuaib, and many more. Perkembangan dan penyebaran karya sastra Arab tidak bisa dilepaskan dari para pelopor dan para tokohnya baik dari negara Arab sendiri maupun dari negara non Arab. Syaikh Adam Abdullah al Ilori adalah salah satu tokoh sastra Arab di Nigeria yang punya peran signifikan dalam penyebaran karya sastra Arab dan sekaligus mencetak generasi penerus sebagai sastrawan dan ahli di bidang sastra Arab di Nigeria. Dalam membentuk generasi sastrawan di bidang sastra Arab (syair), ada lima startegi yang dikembangkan Syaikh Adam al Ilori, yaitu a) dengan cara hafalan, b) mengajarkan karya-karya sastra Arab, c) mengajarkan kaidah-kaidah aruud, d) melatih membuat syair-syair Arab, e) mengadakan kontes-kontes pada momen-momen penting sebagai ajang kreativitas para penyair muda. Lima strategi ini sangat efektif digunakan di Nigeria dalam menyebarkan karya sastra Arab dan membentuk generasi yang ahli di bidang sastra Arab sehingga telah banyak melahirkan sastrawan-sastrawan di Nigeria yang ahli di bidang sastra Arab seperti: Abu Bakar Umar, Roji Suliman, Abdul Baqi Syuaib, dan lain sebagainya.